Motivators for uptake and maintenance of exercise: perceptions of long-term stroke survivors and implications for design of exercise programmes. (1st August 2014) - Poltawski, Leon; Boddy, Kate; Forster, Anne; Goodwin, Victoria A.; Pavey, Amanda C.; Dean, Sarah
Abstract: Purpose : Exercise-after-stroke programmes are increasingly being provided to encourage more physical exercise among stroke survivors, but little is known about what motivates people with stroke to participate in them. This research aimed to identify factors that motivate long-term stroke survivors to exercise, and the implications for programme design. Methods : In two separate studies, focus groups and individual interviews were used to investigate the views of long-term stroke survivors on exercise and participating in exercise programmes. Their data were analysed thematically, and the findings of the studies were synthesised. Results : Eleven stroke survivors and two partners took part in two focus groups; six other stroke survivors (one with a partner) were interviewed individually. Factors reported to influence motivation were the psychological benefits of exercise, a desire to move away from a medicalised approach to exercise, beliefs about stroke recovery, and on-going support to sustain commitment. A number of potential implications of these themes for exercise programme design were identified. Conclusions : A range of personal beliefs and attitudes and external factors may affect the motivation to exercise, and these vary between individuals. Addressing these factors in the design of exercise programmes for long-term stroke survivors may enhance their appeal and so encourage greater engagement in exercise. Implications for Rehabilitation: Exercise programmes may be more attractive to long-term stroke survivors if the psychological well-being benefits of participation are emphasised in their promotion. Some participants will be more attracted by programmes that are de-medicalised, for example, by being located away from clinical settings, and led by or involving suitably-trained non-clinicians. Programmes offered in different formats may attract stroke survivors with different beliefs about the value of exercise in stroke recovery. Programmes should provide explicit support strategies for on-going engagement in exercise.